Clima escolar en una institución educativa de Barranquilla: un estudio desde la percepción estudiantil (2016)
This qualitative study center in describing, understanding, deep, interpretation and construction of sense of school climate expressed in coexistence and social interaction of students of the district school Marie Poussepin the theoretical foundation came from the referents of sociology anspsichology critical, propositional court to establish interactive dialogue between theory and reality addressed the operationalization of the objectives was carried out under the reference of methodological triangulation that investigations of qualitative gives validity and significance of the results and techniques data collection, questionnaires, interviews and observations were used. The results expressed that the school climate is a mentalist social discourse ability to set up a comprehensive theory of mind and an adaptive social discourse. It is argued that the legitimacy of the regulative discourse expressed through teaching and academic psichologicaldecives is critical as competition for change representations and identification with the manual. Students carry out a social construction which is legitimate with pedadogical competence of teachers that from academic discourse, mediates interaction among students. Students construct as a legitimate and valid manual coexistence social reality and transferred in the interactive dynamics of the academic community. The scape of school climate is a transactional and communicative validity claim process is the legitimacy of the semiotics of a social discourse that is only achievable with the participation of the entire educational community.